Closed occlusion due to invagination colon submucosal lipoma - D'Auria, Agustín; Balboa, Oscar; López Susviela, Julio; Torturiello, Horacio; Francia-Volgesang, Eduardo; De Los Santos, Julio (Cirugía del Uruguay, 1982)
Report on a case of closed colonic occlusion caused by colo-colic invagination presenting, at invagination head, a submucosal lipoma of colon and description of its clinical caracteristics. At present it is possible to detect colonic lipomas by double contrast mucosa! relief roentgenography and by fibrocolonoscopy. It is worth high]ighting the fact that this is the first case in our country in which it was possible to resect the tumor isolatedly, without having to resort to colonic excision.